EVALUATION OF ANTIPARKINSONIAN ACTIVITY OF HYDROALCOHOLIC EXTRACT OF THE SEEDS OF VIGNA ACONITIFOLIA IN WISTAR ALBINO RAT - SUSHMITA SINGH,; IMTIYAZ ANSARI, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study is to evaluate the antiparkinsonian activity of hydroalcoholic extract of the seeds of Vigna aconitifolia (HEVA) in Wistar albino rat. Methods: In rats, catalepsy was induced using haloperidol (4 mg/kg i.p.). Treatment groups received bromocriptine (4 mg/kg) and HEVA at the dose of (100, 200, and 300 mg/kg) orally. Bar test for catalepsy, motor coordination test by rotarod, and locomotor activity by actophotometer were carried out to assess behavioral changes. Assay of dopamine and catalase was also carried out to assess biochemical parameters. Results: Bromocriptine and HEVA-treated groups showed a significant difference in behavioral and biochemical parameters as compared to haloperidol control group in the experimental models. Conclusion: Vigna aconitifolia seeds exhibited significant antiparkinsonian activity in haloperidol mouse model.